2018
DOI: 10.1016/j.jtho.2018.08.376
|View full text |Cite
|
Sign up to set email alerts
|

MA08.01 Phase 3 Trial of Whole Brain Radiotherapy with Concurrent Erlotinib Versus WBRT Alone for NSCLC with Brain Metastases (ENTER)

Abstract: trials conversation with their provider. Patients who had not started treatment or were on first-line treatment reported lower discussion rates (30%) than those on later treatment lines (60%). Among patients with follow up, 13 of 20 patients who had not discussed trials with their provider reported doing so after navigation. Ten of eleven patients that had a previous trial conversation initiated an additional one. Primary reasons given for not talking discussing after navigation were having stable disease on a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Interestingly, Professor Wu's AURA3 study on brain metastases published in the Journal of Clinical Oncology in 2018 (25) showed that in the osimertinib group, brain radiotherapy treatment within six months before osimetinib was associated with longer survival compared to no brain radiotherapy. At the World Congress on Lung Cancer 2018 (26), a clinical study compared TKI with brain radiotherapy, and the results showed that TKI combined with WBRT did not benefit patients when compared with WBRT alone. The negative results poured cold water on targeted therapy combined with brain radiotherapy in the era of TKI.…”
Section: Treatment Mode Currently Recommended By Radiotherapymentioning
confidence: 99%
“…Interestingly, Professor Wu's AURA3 study on brain metastases published in the Journal of Clinical Oncology in 2018 (25) showed that in the osimertinib group, brain radiotherapy treatment within six months before osimetinib was associated with longer survival compared to no brain radiotherapy. At the World Congress on Lung Cancer 2018 (26), a clinical study compared TKI with brain radiotherapy, and the results showed that TKI combined with WBRT did not benefit patients when compared with WBRT alone. The negative results poured cold water on targeted therapy combined with brain radiotherapy in the era of TKI.…”
Section: Treatment Mode Currently Recommended By Radiotherapymentioning
confidence: 99%